Endoscopic Ultrasonography-Guided Gallbladder Drainage as a Treatment Option for Acute Cholecystitis after Metal Stent Placement in Malignant Biliary Strictures - Fumisato Kozakai; Yoshihide Kanno; Kei Ito; Shinsuke Koshita; Takahisa Ogawa; Hiroaki Kusunose; Kaori Masu; Toshitaka Sakai; Toji Murabayashi; Keisuke Yonamine; Yujiro Kawakami; Yuki Fujii; et al. (Korean Society of Gastrointestinal Endoscopy, 2019)
Background/Aims It is often difficult to manage acute cholecystitis after metal stent (MS) placement in unresectable malignant biliary strictures. The aim of this study was to evaluate the feasibility of endoscopic ultrasonography-guided gallbladder drainage (EUS-GBD) for acute cholecystitis. Methods The clinical outcomes of 10 patients who underwent EUS-GBD for acute cholecystitis after MS placement between January 2011 and August 2018 were retrospectively evaluated. The procedural outcomes of percutaneous transhepatic gallbladder drainage (PTGBD) with tube placement (n=11 cases) and aspiration (PTGBA) (n=27 cases) during the study period were evaluated as a reference. Results The technical success and clinical effectiveness rates of EUS-GBD were 90% (9/10) and 89% (8/9), respectively. Severe bile leakage that required surgical treatment occurred in one case. Acute cholecystitis recurred after stent dislocation in 38% (3/8) of the cases. Both PTGBD and PTGBA were technically successful in all cases without severe adverse events and clinically effective in 91% and 63% of the cases, respectively. Conclusions EUS-GBD after MS placement was a feasible option for treating acute cholecystitis. However, it was a rescue technique following the established percutaneous intervention in the current setting because of the immature technical methodology, including dedicated devices, which need further development.